Septic shock and multi organ dysfunction in a patient with purulent pericarditis and bacteremia by methicillin-sensitive Staphylococcus aureus. A case-report - Zegarra, Jaime (2021)
Septic shock with multi organ dysfunction is associated with a mortality above 50%. We present here the case of a young male patient who presented with septic shock and multi organ dysfunctions secondary to methicillin- susceptible Staphylococcus aureus from a skin and soft tissue infection presenting with alveolar-nodular pulmonary lesions, purulent pericarditis and septic embolic lesions on the skin, eyes and kidneys. The patient was admitted to the ICU receiving antibiotic coverage with oxacillin and vancomycin, subtotal pericardiectomy and pleural drainage, and was discharged clinically stable. We present this case to draw attention to the severity of S. aureus bacteremia to initiate prompt aggressive therapeutic measures to ameliorate associated morbidity and mortality.